2022
DOI: 10.1021/acs.iecr.2c01898
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Instability of Choline Chloride-Based Deep Eutectic Solvents and Its Influence on Their Toxicity─Important Limitations of DESs as Sustainable Materials

Abstract: Deep eutectic solvents (DESs) have become a hot topic in many branches of science due to their remarkable properties. They have been studied in a wide variety of applications. In particular, choline chloride (ChCl)-based DESs are one of the most commonly used representatives of these fluids. Nevertheless, in order to apply DESs in some fields, it is essential to guarantee their stability, reusability, and biocompatibility. In this context, the long-term stability of three ChCl-based DESs formed using glucose, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 74 publications
2
31
0
Order By: Relevance
“…In the quest to develop sustainable alternative to hydrometallurgical routes for actinide dissolution, RTIL, DES, and other green solvent-based routes are being explored fervently. , Nevertheless, the extent of “greenness” of various RTILs remains an unanswered question. Also, low thermal stability and high viscosity of DESs pose a challenge for routine operations. MSA has been proven to be a highly efficient dissolving media even for industrial operations owing to the high metal salt solubility and stabilization offered to metal ions against aerial oxidation .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the quest to develop sustainable alternative to hydrometallurgical routes for actinide dissolution, RTIL, DES, and other green solvent-based routes are being explored fervently. , Nevertheless, the extent of “greenness” of various RTILs remains an unanswered question. Also, low thermal stability and high viscosity of DESs pose a challenge for routine operations. MSA has been proven to be a highly efficient dissolving media even for industrial operations owing to the high metal salt solubility and stabilization offered to metal ions against aerial oxidation .…”
Section: Resultsmentioning
confidence: 99%
“…18,24−28 Nevertheless, the extent of "greenness" of various RTILs remains an unanswered question. Also, low thermal stability 29 and high viscosity of DESs pose a challenge for routine operations. MSA has been proven to be a highly efficient dissolving media even for industrial operations owing to the high metal salt solubility and stabilization offered to metal ions against aerial oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, by‐products of ChCl degradation such as trimethylamine act as a basic pH buffer and could complicate metal recovery and DES reuse through the formation of metal‐amine complexes [10c,14] . These stability issues are further compounded by the partial esterification of ChCl under common leaching temperatures, [15] making the recycling of the DES phase over multiple cycles a non‐trivial problem as well as affecting its toxicity [15b] . In fact, it was recently suggested that the ChCl : EG DES in the absence of an additional reducing agent will be less efficient for LIB leaching as metal oxide dissolution primarily occurs through the degradation of the DES components at high temperatures [14,16] .…”
Section: Introductionmentioning
confidence: 99%
“…Various classes of DESs have been successfully synthesized thus far. ,, Choline chloride (ChCl)-based DESs, conversely, have demonstrated to be particularly effective because of their low cost, biodegradability, and minimal toxicity. , Electrochemistry, biochemistry, materials science, and petrochemical engineering are just a few of the many fields that have found widespread use for these DESs as solvents or reaction media. Although there has been substantial progress in the study of DESs, the combined experimental and theoretical investigations carried out to obtain the structure and interaction of DESs are limited. These features are widely recognized as being crucial to future DES research and application .…”
Section: Introductionmentioning
confidence: 99%